Identification of T Cell–Mediated Vascular Rejection After Kidney Transplantation by the Combined Measurement of 5 Specific MicroRNAs in Blood. Issue 4 (April 2016) - Matz, Mareen; Fabritius, Katharina; Lorkowski, Christine; Dürr, Michael; Gaedeke, Jens; Durek, Pawel; Grün, Joachim R.; Goestemeyer, Anne; Bachmann, Friederike; Wu, Kaiyin; Rudolph, Birgit; Schmidt, Danilo; et al.
Abstract : Background: MicroRNAs (miRNAs, miR) hold important roles in the posttranscriptional regulation of gene expression. Their function has been correlated with kidney disease, and they might represent a new class of biomarkers for frequent evaluation of renal graft status. We analyzed their potential in identifying severe T cell–mediated vascular rejection (TCMVR) (Banff 4-II/III) in kidney transplanted patients. Methods: Microarray experiments and semiquantitative real-time reverse transcription polymerase chain reaction were performed with total RNA isolated from blood cells of kidney graft recipients. Initial microarray analysis revealed 23 differentially expressed miRNAs distinguishing patients with TCMVR from patients with stable grafts. From these, we validated and further determined the expression of 6 differentially expressed miRNAs and 2 control miRNAs in 161 samples from patients with T cell–mediated rejection (Banff 3-Borderline, Banff 4-I/II/III), Banff-2 antibody-mediated rejection, Banff-5 interstitial fibrosis/tubular atrophy, in samples from stable patients and in samples from patients with urinary tract infection using real-time reverse transcription polymerase chain reaction. Results: Expression levels of all 6 candidate miRNAs were significantly downregulated in blood of TCMVR patients compared to the other groups and displayed high sensitivities and specificities for diagnosing TCMVR. The combination of 5 miRNAs, identified by an unbiased multivariate logistic regression followed by cross-validation, enhanced the sensitivity and specificity for the diagnosis of TCMVR after renal transplantation. Conclusions: The combined measurement of miRNA-15B, miRNA-16, miRNA-103A, miRNA-106A, and miRNA-107 may help to better identify TCMVR after renal transplantation in a precise and clinically applicable way. Abstract : In order to precisely identify patients with acute cellular rejection with severe vascular lesions, the authors demonstrate that 6 peripheral blood miRNAs are selectively downregulated in such patients, while a combination of 5 of them improves sensitivity and specificity to make an accurate diagnosis. Supplemental digital content is available in the text.